2017
DOI: 10.1515/sjecr-2016-0052
|View full text |Cite
|
Sign up to set email alerts
|

Higher Serum Uric Acid Levels in Multiple Sclerosis Patients After Longterm Interferon Beta Treatment

Abstract: Interferon beta is a safe and effi cacious treatment for relapsing multiple sclerosis (MS). However, there is some evidence that uric acid, a scavenger of peroxynitrite, is involved in MS pathology and that increasing serum uric acid levels might have benefi cial therapeutic eff ects. Th e aim of this study is to investigate serum uric acid levels in MS patients (272,31±78,21 μmol/l vs. 210,17±53,65 μmol/l; p=0,019, SAŽETAK Interferon beta je bezbedan i efi kasan lek kod relapsno-remitentnog tipa multiple skl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Furthermore, it has been shown that during treatment with MS immunotherapies, an increased serum UA level was observed. Treatments included glatiramer acetate (Copaxone), interferon-beta (IFNβ) and high-dose methylprednisolone [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that during treatment with MS immunotherapies, an increased serum UA level was observed. Treatments included glatiramer acetate (Copaxone), interferon-beta (IFNβ) and high-dose methylprednisolone [22][23][24].…”
Section: Introductionmentioning
confidence: 99%